Utilization Of Nano Ethanolic Extract Combination Chamber Bitter (Phyllanthus Niruri L.) And Garlic (Allium Sativum L.) As A Natural Immunomodulator In Nanoherbal Development, In Silico And In Vitro Study - Kadek Hendra Darmawan (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2017)
The Filantin compounds in chamber bitter (Phyllanthus niruri L.) and lectin in garlic (Allium sativum L.) was proven as immunomudulatory agents through interaction with Toll-Like Reseptors (TLR) which have role in innate immune responds. Immunomodulators drug available on the market still have many shortcomings such as the low potential. Drug developing by nanotechnology is the right solution to increase the potential of the drug by increasing the absorption and minimize the dose. This research aimed to know the interaction of filantin and lectin with TLR2-TLR1 receptors through molecular docking and produce the nanoemulsion combination of chamber bitter and garlic ethanolic extracts that have phagocytosis activity. In silico assay through molecular docking showed that filantin has affinity for binding to TLR2-TLR1, docking score of lectin (-33,5389) was lower than the filantin (-31.5112). That means lectin has higher affinity for binding to TLR2-TLR1. Nanoemulsion was formulated by SNEDDS methods with composition of co-surfactant: surfactant: oil is 1: 5,25: 1. The nanoemulsion stable at 0,414% (w/v). In vitro assay of phagocytic index (5,03) and ratio (95%) showed that the formulation with nanoemulsion of the combination has higher phagocyte index and ratio than the formulation without nanoemulsion or even the positive controls.